Employer attractiveness, career orientation and self-perceived employability - Meehan, Lauren (My University, 2019)
Human capital is becoming extremely valued in the competitive and dynamic modern working environment. It has thus become very important that employers identify what potential employees find attractive in order to recruit and retain high quality employees. Potential employees’ own career goals, attitudes, and perceived strengths seem likely to play a role in determining what they find attractive in a prospective employer, however there is a need for further research to examine the direct links between these. This research therefore explored the nature of the relationships between different aspects of employer attractiveness and various career orientations, whether any of these various career orientations predicted different aspects of employer attractiveness, and whether these relationships were moderated by self-perceived employability. The study used a quantitative, non-experimental, cross-sectional, correlational design in order to answer the research questions. The sample consisted of 193 third year and postgraduate students registered at the University of the Witwatersrand. All participants were asked to complete a self-developed demographic questionnaire, the Employer Attractiveness (EmpAt) scale, the Career Orientation scale, and the Self-perceived Employability scale. Data analyses run to answer the research questions included reliability calculations, descriptive statistics, correlations, multiple regression, and moderated multiple regression. The results showed that there were significant relationships between the different aspects of employer attractiveness, the various career orientations, and self-perceived employability. Development value was significantly predicted by the security and technical/functional career orientations. Social value was significantly predicted by the entrepreneurial creativity, service to a cause, lifestyle, and technical/functional career orientations. Interest value was significantly predicted by the entrepreneurial creativity, service to a cause, and technical/functional career orientations. Application value was significantly predicted by the entrepreneurial creativity, service to a cause, security, and technical/functional career orientations. Lastly, economic value was significantly predicted by the entrepreneurial creativity, lifestyle, managerial, and security career orientations. Self-perceived employability did not moderate any of the relationships between the different aspects of employer attractiveness and the various career orientations. The findings of the study are useful as they contribute to existing theory and can be used to inform recruitment practice and help companies to tailor their strategies to attract and retain high quality potential employees.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Psychology by Coursework and Research Report (in the field of Organisational Psychology) in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 15 March 2019.
Keywords: Human capital; Personnel management